2009
DOI: 10.1007/978-3-642-04271-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cerebral Cortical Folding: Multivariate Complexity-Shape Analysis with Insights into Handling Brain-Volume Differences

Abstract: Abstract. This paper presents a study of gender differences in adult human cerebral cortical folding patterns. The study employs a new multivariate statistical descriptor for analyzing folding patterns in a region of interest (ROI) and a rigorous nonparametric permutation-based scheme for hypothesis testing. Unlike typical ROI-based methods that summarize folding complexity or shape by single/few numbers, the proposed descriptor systematically constructs a unified description of complexity and shape in a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
3
8
1
Order By: Relevance
“…Finally, statistical analysis involves the analyses of shape and microstructure both individually and jointly. The latter employs a novel multivariate inference technique based on the analysis of the joint probability density function (pdf) of the feature set whose efficacy has been demonstrated in a cortical folding study of neonatal brains using the joint analysis of folding complexity and shape indices (Awate et al, 2009b,a). In the following, we discuss each component in detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, statistical analysis involves the analyses of shape and microstructure both individually and jointly. The latter employs a novel multivariate inference technique based on the analysis of the joint probability density function (pdf) of the feature set whose efficacy has been demonstrated in a cortical folding study of neonatal brains using the joint analysis of folding complexity and shape indices (Awate et al, 2009b,a). In the following, we discuss each component in detail.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we utilize a novel multivariate analysis (Awate et al, 2009b,a) to directly exploit the relationship between thickness and diffusion properties. Specifically, for each subject, we build a joint probability density function (pdf) of thickness and diffusion properties which captures the interdependencies of thickness and diffusion features as provided solely by the data.…”
Section: Methodsmentioning
confidence: 99%
“…The FD can also be applied to measure cortical folding complexity, and previous studies have shown significant differences in regional FD for psychiatric disorders such as schizophrenia (Casanova et al, 1989;Narr et al, 2004;Narr et al, 2001), obsessive-compulsive disorder (Ha et al, 2005), epilepsy (Free et al, 1996), Alzheimer's disease (King et al, 2009(King et al, , 2010, multiple sclerosis (Esteban et al, 2007s, 2009, cerebellar degeneration , stroke (Zhang et al, 2008a), autism (Awate et al, 2008), and Williams syndrome (Thompson et al, 2005), as well as for normal development (Awate et al, 2010;Blanton et al, 2001;Kalmanti and Maris, 2007;Shyu et al, 2010;Wu et al, 2009), early-life blindness (Zhang et al, 2008b), and IQ (Im et al, 2006). Furthermore, some studies report local FD or folding differences for genetic factors such as 22q11 deletion syndrome (Schaer et al, 2008), gender (Awate et al, 2009;Luders et al, 2004), and brain size (Toro et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…CC increases in the early life, with regional differences in a caudo‐rostral gradient, and then undergoes a progressive decrease [Blanton et al, ; Magnotta et al, ; Zilles et al, 1988]. As reported, CC is greater in women frontal and parietal lobes [Awate et al, ; Luders et al, 2004, ,b, 2008; Nopoulos et al, ; Zilles et al, ].…”
Section: Introductionmentioning
confidence: 99%